Geografia e Inteligência Territorial: conceitos, métodos e práticas aplicados à pesquisa em Segurança Hídrica - Raimundo Nonato Junior (Confins)
This article presents the concept of territorial intelligence, the effects of territorial learning and the notion of Geoinnovation based on tangible and intangible assets, discussed from the perspective of contemporary Geographical Science, dialoguing with concepts and methods that make up the perspective referred to by the author as Knowledge Geography. These foundations served as the basis for the Water Security Panel (PSH) research project, with a view to linking theory and practice between Geography and Information Technology. The text also situates this discussion within the thematic scenario of water security and highlights the challenges for territorial innovation in this area. The main results point to the development of five methodological groups of innovative actions developed for public policies (integrated geospatial data management, Smart GeoLayers geotechnology platform, interactive dashboards, dynamic data module and analytical prognosis).